Ultrastructural Alterations in the Midgut of Diplopods after Subchronic Exposure to Substrate Containing Sewage Mud - Nogarol, Larissa Rosa [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Springer, 2011)
The use of sewage mud in agriculture has generated several discussions due to the risks of soil contamination mainly by metals. Due to the intimate contact of the diplopods with soil, they have been successfully used in ecotoxicological analyses. The impact of the external environment in the physiological changes in organs and tissues of different organisms can be reflected by the ultrastructural changes of their cells. Using the transmission electron microscopy, this study aimed to analyze the ultrastructural alterations in the midgut of the diplopod Rhinocricus padbergi exposed to substrate containing sewage mud from a Sewage Treatment Station of So Paulo State, Brazil. Therefore, it was sought to identify cellular alterations resulting from the subchronic exposure (90 days of exposure) of the animals to complex and potentially toxic mixtures such as sewage mud at different concentrations (1%, 10%, and 50%). The control group presented integrity in the cells and tissues that constitute the midgut. The animals exposed to sewage mud at 10% and 50% died before the 90 days of exposure. The analysis of the midgut of the animals exposed to 1% of sewage mud showed alterations in the epithelial cells, cells of the fat body layer, and hepatic cells. The main alterations observed were cytoplasmatic vacuolization, loss of the plasmatic membrane, and nuclear envelope integrity. We conclude that the mud sample presents a mixture of complex substances of cytotoxic and genotoxic action to the diplopod, causing cell death, since both the nucleus and other cellular compartments were damaged.
Keywords: Millipedes; STS; Digestive tract; TEM; Toxicity